2019
DOI: 10.1371/journal.pone.0216547
|View full text |Cite
|
Sign up to set email alerts
|

Higher dietary acid load potentially increases serum triglyceride and obesity prevalence in adults: An updated systematic review and meta-analysis

Abstract: Background In the current meta-analysis, we aimed to systematically review and summarize the eligible studies evaluating the association between dietary acid load in terms of potential renal acid load (PRAL) and net-endogenous acid production (NEAP) with anthropometric parameters and serum lipids in adult population. Methods In a systematic search from PubMed, Scopus, Web of Sciences and Cochrane electronic databases up to December 2018, relevant studies were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…Diets high in acid induce metabolic acidosis, which can lead to hypertension, CKD, insulin resistance, diabetes, and other complications (20). A high dietary acid load has also been linked to obesity (22).…”
Section: Role Of Food Deserts On Hypertension and Chronic Kidney Diseasementioning
confidence: 99%
“…Diets high in acid induce metabolic acidosis, which can lead to hypertension, CKD, insulin resistance, diabetes, and other complications (20). A high dietary acid load has also been linked to obesity (22).…”
Section: Role Of Food Deserts On Hypertension and Chronic Kidney Diseasementioning
confidence: 99%
“…Bahadoran et al, supported that both PRAL and Pro/k scores were positively associated with TG and inversely associated with HDL‐C 58 . A recently published systematic review and meta‐analysis of 17 observational studies reported that the highest category of PRAL scores was associated with higher TG 59 . In contrast, a cross‐sectional study by Mukarami et al, on 1136 female Japanese dietetic students aged 18‐22 years found that PRAL was directly associated with total cholesterol and LDL, but there was no association between PRAL and TG 60 .…”
Section: Discussionmentioning
confidence: 94%
“…[15,16] Metabolic acidosis can be calculated through the potential renal acid load (PRAL) [15] and net endogenous acid production (NEAP) [16] formulas, which are validated and straightforward methods to estimate the dietary acid load from diet-composition data. A prolonged diet-induced low-grade metabolic acidosis over the years may predispose to metabolic abnormalities, in particular, insulin resistance, diabetes, high serum triglycerides, and obesity [17,18]. Consequently, the production of insulin-like growth factor-1 (IGF-I) probably increases [19], which, in turn, is associated with an increased BC risk [20].…”
Section: Introductionmentioning
confidence: 99%